Favourable outcome of Fusarium prosthetic valve endocarditis in a patient with an Ebstein anomaly - Scott G. Lee-Jones; Stefan Van der Westhuizen; Johannes Taljaard; Nelesh P. Govender; Rubina Razack (Southern African Journal of Infectious Diseases)
Fungal endocarditis is rare, challenging to diagnose and treat and associated with high mortality. We describe a case of Fusarium solani endocarditis in a patient with Ebstein’s anomaly with a favourable outcome.